PERAN PENDIDIKAN AKUNTANSI SYARIAH DALAM MEMBENTUK ETIKA PROFESIONAL MAHASISWA AKUNTANSI - Rini Muflihah (LPPM IAIT, 2025)
This study aims to examine the role of Islamic accounting education in shaping the professional ethics of accounting students in Indonesia. Using a quantitative approach, data were collected through questionnaires distributed to 300 students majoring in accounting who took Islamic accounting courses. The results showed that Islamic accounting education has a significant influence on the formation of students' professional ethics. Students who have a good understanding of sharia principles, such as the prohibition of riba, gharar, and maysir, tend to prioritize ethical values in accounting practices, such as integrity, transparency, and fairness. However, the results also show that the application of these principles in the working world is still limited, which indicates the need for further development in the curriculum and teaching methods. This study provides an important contribution to the development of Islamic accounting education curriculum that is more effective in shaping high professional ethics in students